Help-seeking for mental health concerns: review of Indian research and emergent insights - Prachi Bhavesh Sanghvi; Seema Mehrotra (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this review was to examine Indian research on help-seeking for mental health problems in adults. Design/methodology/approach - Original Indian research studies on help-seeking for mental health, published from the year 2001-2019 were searched on PubMed, EBSCO, ProQuest and OVID using a set of relevant keywords. After applying exclusion criteria, 52 relevant research studies were identified. Findings - The reviewed studies spanned a variety of themes such as barriers and facilitators to help-seeking, sources of help-seeking, causal attributions as well as other correlates of help-seeking, process of help-seeking and interventions to increase help-seeking. The majority of these studies were carried out in general community samples or treatment-seeking samples. Very few studies incorporated non-treatment seeking distressed samples. There is a severe dearth of studies on interventions to improve help-seeking. Studies indicate multiple barriers to seeking professional help and highlight that mere knowledge about illness and availability of professional services may be insufficient to minimize delays in professional help-seeking. Originality/value - Help-seeking in the Indian context is often a family-based decision-making process. Multi-pronged help-seeking interventions that include components aimed at reducing barriers experienced by non-treatment seeking distressed persons and empowering informal support providers with knowledge and skills for encouraging professional help-seeking in their significant others may be useful.